Discussion on requirements of gasifier gas tightness for underground coal gasification production. (October 2021) - Feng, Mingze; Xin, Lin; ZhigangWang,; Li, Kaixuan; Wu, Jing; Li, Jiaze; Cheng, Weimin; Wang, Bowei
Abstract: Underground coal gasification (UCG) technology is an innovative coal in-situ chemical combustion mining method. Affected by complex geological conditions and poor controllability, UCG has not yet realized large-scale industrial application. The gas tightness control of UCG is an important factor to ensure its safe production, but there are deficiencies in its research at this stage. In the process of UCG, complex physical and chemical changes will occur in the overburden of the gasifier under high temperature, resulting in thermal damage and fracture development of the overburden, which makes it difficult for the underground gasifier to maintain good gas tightness. In this paper, the important significance of gas tightness to underground gasifier, the influencing factors of gas tightness and how to detect and maintain gas tightness were discussed, and some suggestions were also put forward on how to reduce gas leakage and improve gas tightness.